2005
DOI: 10.1111/j.1742-7843.2005.pto960405.x
|View full text |Cite
|
Sign up to set email alerts
|

2,3‐Dimercapto‐1‐propanol does Not Alter the Porphobilinogen Synthase Inhibition but Decreases the Mercury Content in Liver and Kidney of Suckling Rats Exposed to HgCl2

Abstract: Heavy metals have received great attention as environmental pollutants mainly because once introduced in the biological cycle they are incorporated in the food chain. Especially the mercury toxicity due to a diversity of effects caused by different chemical species should be emphasized. Heavy metal intoxication has been treated with chelating agents such as 2,3-dimercapto-1-propanol (BAL). However, the efficacy of this treatment is questionable due to the lack of specific effect on the toxic metal. The present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…Among toxic metals, mercury, a divalent metal without any biological function, causes several deleterious effects in adults (Emanuelli et al, 1996;Shigematsu et al, 2000) and developing organisms (Peixoto et al, 2003(Peixoto et al, , 2004Roza et al, 2005) which primarily affect the central nervous (Pereira et al, 1999;Rocha et al, 2001; and renal systems (Magos et al, 1974;Emanuelli et al, 1996;. Young animals, mainly during the first days after birth, seem to be more sensitive than adults to toxic agents (Null et al, 1973;Jugo, 1976;Nielsen and Andersen, 1996).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Among toxic metals, mercury, a divalent metal without any biological function, causes several deleterious effects in adults (Emanuelli et al, 1996;Shigematsu et al, 2000) and developing organisms (Peixoto et al, 2003(Peixoto et al, , 2004Roza et al, 2005) which primarily affect the central nervous (Pereira et al, 1999;Rocha et al, 2001; and renal systems (Magos et al, 1974;Emanuelli et al, 1996;. Young animals, mainly during the first days after birth, seem to be more sensitive than adults to toxic agents (Null et al, 1973;Jugo, 1976;Nielsen and Andersen, 1996).…”
Section: Introductionmentioning
confidence: 97%
“…Using young rats as models, results from the literature and from this group have demonstrated that exposure to HgCl 2 (25 mg/kg) for five consecutive days causes cerebral (Rocha et al, 1995;Roza et al, 2005) and corporal weight losses (Rocha et al, 1995;Peixoto et al, 2003), renal weight increase (Rocha et al, 1995;Peixoto et al, 2003;Roza et al, 2005), mercury accumulation in tissues (Peixoto et al, 2003;Roza et al, 2005), inhibition of porphobilinogen synthase activity (Rocha et al, 1995;Peixoto et al, 2003;Roza et al, 2005), alterations in renal and hepatic functions and glycemia . Zinc pre-treatment prevents or alleviates most of these toxic effects (Peixoto et al, 2003;.…”
Section: Introductionmentioning
confidence: 97%
“…Heavy metals such as mercury (Hg), which is added to skin-whitening cosmetics, may cause acute or chronic damage to human cells. Hg, a divalent metal with no known biological function, may cause several deleterious effects in adults (1,2), as well as in developing organisms (3,4), which primarily involve the central nervous system (5-7) and the kidneys (1,8,9). Young animals seem to be more sensitive to Hg toxicity than adults, particularly during the first days following birth.…”
Section: Introductionmentioning
confidence: 99%
“…The high affinity of Hg(II) for sulfur-containing biomolecules, in particular, proteins with cysteine residues, has been proposed to inhibit or deactivate the biological function of several enzymes [19,20]. Various well known chelating agents such as D-penicillamine (H 2 Pen@HSC(CH 3 ) 2 -CH(NH 3 ) + COO À ) and BAL (2,3-dimercaptopropanol) have been clinically used for detoxification and efficiently reduce plasma levels of Hg(II) [19][20][21]. Often, very stable forms include linear complexes with two sulfur ligands; nevertheless, the Hg-S bonds are labile and for higher coordination numbers the structures are flexible, often with distorted trigonal or tetrahedral coordination geometries [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Absorption of mercury in human body causes several damages to the central nervous system, DNA, mitosis and endocrine system [14][15][16][17][18]. The high affinity of Hg(II) for sulfur-containing biomolecules, in particular, proteins with cysteine residues, has been proposed to inhibit or deactivate the biological function of several enzymes [19,20]. Various well known chelating agents such as D-penicillamine (H 2 Pen@HSC(CH 3 ) 2 -CH(NH 3 ) + COO À ) and BAL (2,3-dimercaptopropanol) have been clinically used for detoxification and efficiently reduce plasma levels of Hg(II) [19][20][21].…”
Section: Introductionmentioning
confidence: 99%